The Challenges of the Anti-Open Grazing Laws in Nigeria - Ifenna Leonard Azomani; Peter Ikechukwu Gasiokwu (UIN Sunan Gunung Djati, 2025)
Open grazing, the traditional practice of moving livestock freely across regions in Nigeria, has contributed significantly to rising insecurity, farmer-herder conflicts, and environmental degradation. In response to the Federal Government's inaction, several Nigerian states have enacted Anti-Open Grazing Laws to regulate the practice. This article critically examines the legal, political, and environmental challenges posed by these laws, with particular reference to the Delta State Livestock Breeding and Marketing Regulation Law, 2021. Using a doctrinal legal methodology, this study analyses statutory texts, judicial decisions, and scholarly commentaries. It finds that while these laws offer a regulatory framework for livestock management, their implementation is hampered by questions of constitutional competence, weak enforcement mechanisms, political resistance, and the exclusion of nomadic pastoralist perspectives. The paper further reveals that the federal government’s opposition to state-level grazing laws exacerbates ethno-regional tensions, especially due to the socio-cultural identity of nomadic herders. The study concludes that while state legislation is constitutionally permissible under the concurrent legislative list, a harmonized federal framework incorporating customary law, socio-economic realities, and inclusive stakeholder consultation is essential for a sustainable solution.